O CINEMA COMO TERRITÓRIO DO ARMÁRIO: Cidade, corpo e representações contemporâneas - Bousada, Tadeu Barbuto (2021)
This research discusses the relationships between cinema and the closet, having as object of analysis, three contemporaryBrazilian films: Tattoo (Tatuagem, 2013, Hilton Lacerda), Futuro Beach (Praia do Futuro, 2014, Karim Aïnouz) and The Way He Looks (Hoj